Optimization and evaluation of Luminex performance with supernatants of antigen-stimulated peripheral blood mononuclear cells. (December 2016) - Surenaud, Mathieu; Manier, Céline; Richert, Laura; Thiébaut, Rodolphe; Levy, Yves; Hue, Sophie; Lacabaratz, Christine
Abstract Background The Luminex bead-based multiplex assay is useful for quantifying immune mediators such as cytokines and chemokines. Cross-comparisons of reagents for this technique from different suppliers have already been performed using serum or plasma but rarely with supernatants collected from antigen-stimulated peripheral blood mononuclear cells (PBMC). Here, we first describe an optimization protocol for cell culture including quantity of cells and culture duration to obtain reproducible cytokine and chemokine quantifications. Then, we compared three different Luminex kit suppliers. Results Intraclass correlation coefficients (ICCs) for a 2-days stimulation protocol were >0.8 for IFNγ and Perforin. The specific concentration was maximal after two or five days of stimulation, depending on the analyte, using 0.5 million PBMC per well, a cell quantity that gave the same level of specific cytokine secretion as 1.0 million. In the second part of the study, Luminex kits from Millipore showed a better working range than Bio-Rad and Ozyme ones. For tuberculin purified protein derivative (PPD)-stimulated samples, the overall mean pooled coefficients of variation (CVs) for all donors and all cytokines was 17.2 % for Bio-Rad, 19.4 % for Millipore and 26.7 % for Ozyme. Although the different kits gave cytokine concentrations that were generally compatible, there were discrepancies for particular cytokines. Finally, evaluation of precision and reproducibility of a 15-plex Millipore kit using a "home-made" internal control showed a mean intra-assay CV <13 % and an inter-assay CV <18 % for each cytokine concentration. Conclusions A protocol with a single round of stimulation but with two time points gave the best results for assaying different cytokines. Millipore kits appear to be slightly more sensitive than those from Bio-Rad and Ozyme. However, we conclude that the panel of analytes that need to be quantified should be the main determinant of kit selection. Using an internal control we demonstrated that a 15-plex magnetic Milliplex kit displayed good precision and reproducibility. Our findings should help optimize assays for evaluating immune responses during the course of disease or infection, or in response to vaccine or therapy.